Chile : Technical Assistance Report-Assessment of Tax Expenditures and Corrective Taxes. (IMF Staff Country Reports; Country Report, 2020)
In response to a request from Mr. Ignacio Briones Rojas, Minister of Finance of Chile, a remote mission was conducted by a joint team of staff from the International Monetary Fund (IMF) and the secretariat of the Organisation for Economic Co-operation and Development (OECD) during April - October 2020. The mission's main purpose was to assist the Minister of Finance with technical support to review Chile's tax expenditure methodology and its corrective excise taxes. The present report reflects the findings of the mission. This report was written jointly by the IMF and the OECD, with the IMF team leading the work assessing tax expenditures in the corporate income tax (CIT) and the analysis of excises, and the OECD team leading the work assessing tax expenditures in the personal income tax (PIT) and value added tax (VAT). A presentation of the main findings was given to the Minister of Finance on October 6, 2020. The report incorporates comments provided by the Ministry and the Chilean Revenue Administration.